Pengetahuan Remaja Putri Tentang Menarche Berdasarkan Sumber Informasi Tahun 2019 - Mela Mustika Sari; Fatmawati Karim (Akademi Kebidanan La Tansa Mashiro, 2020)
Adolescence is the process of going through puberty which is the stage of an individual growing up. The most important event that occurs in teenage girls is the arrival of the first menstruation which is called menarche purposes, Know the Knowledge Description of Class V and VI Young Girls about Menarche Based on Information Sources at Gunung Tua Public Elementary School in the March-April 2019 Period. methods, used a descriptive research method and the type of data used in this study was primary data, namely data obtained directly from research respondents, namely young girls in grades V and VI at SD Negeri Gunung Tua in 2019 with an initial population of 52 female students and sampling with Total Sampling technique.result illustrates that more than half, namely 26 respondents (57.8%) received information about menarche directly and more than half, namely 5 respondents (71.4%) received information about menarche indirectly, conclussion Teenagers tend to get information about menarche indirectly (print media, electronic media), this is because electronic media is media that is able to spread news quickly.